Potent Plant Extracts: Combatting Potato Tuber Soft Rot Disease Caused by Pectobacterium carotovorum subsp. carotovorum: control of bacterial soft rot of potato - almasoudi, Najeeb; Adel D. Al-Qurashi , Dr; Abo, kamal (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
The objective of this research was to assess the efficacy of three plant extracts—Cumin, pomegranate, and Black pepper against Pectobacterium carotovorum subsp. carotovorum, a bacterium responsible for causing soft rot disease in potato tubers. This ailment poses a significant threat to potato production, impacting the quality of potatoes throughout storage, transit, and shipment. To conduct the investigation, twenty isolates of the pathogenic bacterium were acquired from naturally infected potato tubers and identified as P. carotovorum subsp. carotovorum through various microbiological characteristics. Through in vitro experiments, the plant extracts were examined for their antibacterial properties against the bacterium. The findings revealed that all three plants extract exhibited inhibition of bacterial growth. Notably, pomegranate demonstrated the most potent inhibitory effect among the three extracts. In light of these in vitro results, it is recommended to employ all extracts at a concentration of 50 mg to effectively control soft rot disease in potato tubers during storage. The concentration of 50 mg was identified as the most effective in impeding the growth of the pathogenic bacterium. In summary, this study demonstrated the potential of all tested plant extracts to mitigate potato tuber soft rot disease, addressing a significant challenge in potato production.